L’écologisation, mise à l’épreuve ou nouveau registre de légitimation de l’ordre territorial ? - Vincent Banos; Anne Gassiat; Sabine Girard; Baptiste Hautdidier; Marie Houdart; Sophie Le Floch; Françoise Vernier (Développement Durable et Territoires)
Our aim is to contribute to a debate, initially framed in the french context, on how dominant principles of « territorialization » may be undergoing an ecological turn. Drawing on a critical review of the literature, we propose first an analytical framework built around three major nodes of the debate : materialities, narratives, organizations. We then test this framework on a diversity of case study areas, explored in the context of our respective research works. This leads us to identify three archetypical settings of the territorial effects of « greening » processes : « a-territorial », « alibi », « emancipatory ». We end by discussing how « greening » unevenly triggers and combines the tenets of territorialization, whether by consolidating or challenging the current « territorial order ».